Menghidupi Kesalehan di Panggung Global: Personal Branding, Narasi Kultural, dan Pembentukan Reputasi Dian Pelangi dalam Industri Mode Muslim - Yunus, Hesty Ananta; Nasution, Yenni Samri Juliati; Daulay, Aqwa Naser (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study examines how Dian Pelangi, a prominent Indonesian modest fashion designer, develops her global brand in the Muslim fashion industry. Using qualitative content analysis of social media and digital publications within the STP framework (Segmentation, Targeting, Positioning), the research shows that she targets digitally literate Muslim women aged 18 to 40 and middle to upper class Muslims, expanding her reach to the global diaspora through collaborations with international designers and institutions. She positions herself as a pioneer of Indonesian modest fashion by integrating religious values, global trends, and local heritage such as batik and tenun. Her reputation is strengthened through participation in international events including New York Fashion Week, Istanbul Modest Fashion Week, and recognition in Forbes 30 Under 30 Asia. Digital analysis indicates that her New York Fashion Week content generated the highest engagement with 51600 views and 497 comments, highlighting the importance of global visibility.